Efek asam alfa lipoat terhadap insulitis pada tikus diabetes melitus tipe 2 - Ismawati Ismawati; Mukhyarjon Mukhyarjon; Ilhami Romus; Sonia Dinda Paramitha (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2019)
Effect of alpha lipoic acid on insulitis in type 2 diabetic ratBackground: The damaging of β cell causes hyperglycemia. Β cell damaged as insulitis happens because of the increase of free radical and the decrease of endogen antioxidant that caused oxidative stress.Objective: The goal of this research was to find out the effect of alpha lipoic acid (ALA) on pancreas Langerhans island’s histopathology in type 2 diabetic rats.Methods: This was an experimental laboratory study with post test only design. Fifteen adult male rats of Wistar strain were segregated into three groups (n=5) labeled as control, type 2 diabetes (DM), and DM+ALA. The experiment was designed for 3 weeks. The measured parameter was insulitis level on pancreas Langerhans island of groups labeled.Results: The statistical test result showed there was the significant difference between control and type 2 diabetes group (p=0,005), but there was no significant difference between DM and DM+ ALA group (p=0,549).Conclusions: Although not statistically significant, giving ALA 60 mg/kg body weight for 3 weeks decreased the degree of insulitis in diabetic rats.